Madilog dan Sains Pembebasan: Relevansi Epistemologi Tan Malaka Bagi Pendidikan Kritis di Indonesia - Hidayat, Arief (Jurnal Syntax Fusion, 2024)
This study examines the relevance of the epistemology of Madilog (Materialism-Dialectics-Logic) by Tan Malaka in the context of critical education in contemporary Indonesia. Madilog, which emphasizes rational and scientific thinking based on dialectical materialism, offers a strong theoretical foundation for liberating individuals from dogmatic and mystical thinking. Through a qualitative descriptive approach and content analysis methodology, this research aims to explore how the principles of Madilog can be applied in education in Indonesia, particularly to foster critical consciousness among students. The findings indicate that Madilog can be integrated into critical education through the application of dialectical principles that encourage students to analyze and critique social injustices, while recognizing the potential for social change through collective action. However, its implementation faces challenges, including the dominance of cultural and religious values in Indonesia and limitations within the existing education curriculum. This study suggests the need for adapting Madilog to the local context and structural changes in the educational system to ensure the liberation and empowerment of students through critical education. Thus, Madilog offers significant contributions to the development of education that is more critical, rational, and aligned with social justice.